In-situ observation of damage evolution in polycarbonate subjected to hypervelocity impact. (August 2020) - Kawai, Nobuaki; Nagano, Mikio; Hasegawa, Sunao; Sato, Eiichi
Highlights: Succeeded in the sub-μs time-resolved imaging of the impact-induced damage evolution. Evolution of damage texture is visualized by the scattered-light imaging method. Propagation of stress field is visualized by the cross-polarized shadowgraphy. Abstract: Hypervelocity impact experiments were performed on polycarbonates to investigate the progress of the impact-induced damage process inside the polymer material. Damage evolution and stress wave propagation associated with hypervelocity impact were observed by two imaging methods using ultra-high-speed cameras. The first was two-directional (side-view and rear-view) scattered light imaging. Time-resolved images obtained provided information about the three-dimensional time evolution of not only the damage development, but also the damage texture. The second was cross-polarized shadowgraphs. In this measurement, propagation of the stress field was clearly visualized. The results obtained in this study clearly indicate that the combination of various imaging methods, where each one can provide different information, is a useful way to obtain insights into the damage process and mechanism associated with hypervelocity impact.